Consideraciones en torno a la prueba indiciaria - Vidaurri Aréchiga, Manuel (2019)
The so-called prima facie evidence (also called conjectural or circumstantial evidence) has not received adequate attention within the framework of the general theory of evidence. This text seeks to highlight aspects related to its structure, functions, and scope. Eventually, this type of legal proof could support a condemnatory or acquittal court resolutions, a situation that in both cases claims for emphasizing its importance.